2018
DOI: 10.3390/pr6050053
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Framework for Data Management and Integration in a Continuous Pharmaceutical Manufacturing Processing Line

Abstract: As the pharmaceutical industry seeks more efficient methods for the production of higher value therapeutics, the associated data analysis, data visualization, and predictive modeling require dependable data origination, management, transfer, and integration. As a result, the management and integration of data in a consistent, organized, and reliable manner is a big challenge for the pharmaceutical industry. In this work, an ontological information infrastructure is developed to integrate data within manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Cloud‐based data lakes such as Amazon Web Services and Microsoft Azure are some of the most common solutions (Scheitz, Peck, & Groban, 2018). Cao et al (2018) reported the development of an ontological information infrastructure to integrate data within manufacturing plants and analytical laboratories with the adaptation of ANSI/ISA‐88.01 batch control standard.…”
Section: Data Automation Visualization and Smart Data Utilitymentioning
confidence: 99%
“…Cloud‐based data lakes such as Amazon Web Services and Microsoft Azure are some of the most common solutions (Scheitz, Peck, & Groban, 2018). Cao et al (2018) reported the development of an ontological information infrastructure to integrate data within manufacturing plants and analytical laboratories with the adaptation of ANSI/ISA‐88.01 batch control standard.…”
Section: Data Automation Visualization and Smart Data Utilitymentioning
confidence: 99%
“…PMS are uniquely positioned between analytical and bioprocess interface to enable not only automated data analysis and visualization but also to control analytical and process instruments for feedback or feedforward control (Figure 5). 14 Cao et al reported the development of an ontological information 71 This study demonstrated a well-defined data structure, where all the detailed information including metadata were documented in a recipe model and it was connected to PMS, DCS, ELN, LES, and cloud storage for improved data communication. 71 Most of the PMS modules contain in-built databases (Oracle or SQL servers) for handling larger data sets such as vibrational spectroscopic data which is typically used as a temporary data storage solution.…”
Section: Data Management and Visualizationmentioning
confidence: 99%
“…14 Cao et al reported the development of an ontological information 71 This study demonstrated a well-defined data structure, where all the detailed information including metadata were documented in a recipe model and it was connected to PMS, DCS, ELN, LES, and cloud storage for improved data communication. 71 Most of the PMS modules contain in-built databases (Oracle or SQL servers) for handling larger data sets such as vibrational spectroscopic data which is typically used as a temporary data storage solution. 72 As shown in Figure 4, we used a PMS platform to automatically shuttle Mid-IR spectra, followed by analysis and visualization in the graphical user interface.…”
Section: Data Management and Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Two contributions focus on challenges in pharmaceutical manufacturing. The first paper describes the development of a database of multiphase reactions for synthesizing small-molecule pharmaceutical to facilitate investigation of reaction-separation schemes [11], while the second paper provides a complementary study on developing an ontological information infrastructure for integrating data from pharmaceutical manufacturing plants and analytical laboratories [12]. The Special Issue also contains two contributions focusing on polymerization processes.…”
Section: Materials Processesmentioning
confidence: 99%